Estimated HIV Incidence in the United States, 2003–2010. (1st January 2017) - Xia, Qiang; Teixeira-Pinto, Armando; Forgione, Lisa A.; Wiewel, Ellen W.; Braunstein, Sarah L.; Torian, Lucia V.
Abstract : Objective: To estimate HIV incidence in the United States using a newly developed method. Methods: The analysis period (2002–2011) was broken down into 3-year periods with overlaps, and HIV incidence was estimated based on the relationship between number of new diagnoses and HIV incidence in each of these 3-year periods, by assuming that all HIV infections would eventually be diagnosed and within each 3-year period HIV incidence and case finding were stable. Results: The estimated HIV incidence in the United States decreased from 52, 721 (range: 47, 449–57, 993) in 2003 to 39, 651 (range: 35, 686–43, 617) in 2010, among males from 38, 164 (range: 35, 051–42, 840) to 33, 035 (range: 29, 088–35, 553), and among females from 13, 557 (range: 12, 133–14, 830) to 6616 (range: 5825 to 7120). Conclusions: Using a simple and novel method based on the number of new HIV diagnoses, we were able to estimate HIV incidence and report a declining trend in HIV incidence in the United States since 2003. Abstract : Supplemental Digital Content is Available in the Text.